2011
DOI: 10.1093/carcin/bgr068
|View full text |Cite
|
Sign up to set email alerts
|

TRIM40 promotes neddylation of IKK  and is downregulated in gastrointestinal cancers

Abstract: Gastrointestinal neoplasia seems to be a common consequence of chronic inflammation in the gastrointestinal epithelium. Nuclear factor-kappaB (NF-κB) is an important transcription factor for carcinogenesis in chronic inflammatory diseases and plays a key role in promoting inflammation-associated carcinoma in the gastrointestinal tract. Activation of NF-κB is regulated by several posttranslational modifications including phosphorylation, ubiquitination and neddylation. In this study, we showed that tripartite m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 43 publications
0
77
0
2
Order By: Relevance
“…Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32]. Thus, it is important to clarify the correlation between the functions of TRIM family ubiquitin ligases and the effects of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32]. Thus, it is important to clarify the correlation between the functions of TRIM family ubiquitin ligases and the effects of these signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we revealed that TRIM40, which is also one of the TRIM family ubiquitin ligases, enhanced neddylation of inhibitor of kappa B (I B) kinase (IKK) and inhibited the activity of NF-B-mediated transcription [28]. It has been reported that TRIM45 suppresses transcriptional activities of E twenty-six (ETS)-like transcription factor 1 (Elk-1) and activator protein 1 (AP-1), which are targets of the MAPK signaling pathway [23].…”
Section: Trim45 Negatively Regulates Tnf -Induced Nf-b-mediated Transmentioning
confidence: 99%
“…For example, we revealed that TRIM40, which is one of the TRIM family of ubiquitin ligases, enhances neddylation of IKKγ and inhibits the activity of NFκB-mediated transcription [25]. Moreover, we found that TRIM59 interacts with a signal adaptor protein, evolutionarily conserved signaling intermediate in Toll pathways (ECSIT), and negatively regulates NFκB and IRF3/7 signal pathways [24].…”
Section: Trim39 Negatively Regulates Nfκb Signalingmentioning
confidence: 97%
“…Based on our previous findings that some of the TRIM family proteins affect the stabilities of their binding proteins [13,14,[24][25][26], we speculated that TRIM39 affects the stability of Cactin. Although we assumed that TRIM39 promotes degradation of Cactin, protein stability analysis with cycloheximide revealed that overexpression of TRIM39 WT or that of ΔRING promoted the stabilization of Cactin protein (Fig.…”
Section: Trim39 Stabilizes Cactinmentioning
confidence: 99%
“…TRIM26 is a member of the tripartite motif (TRIM) protein family composed of more than 70 members in human 29. In recent years, the TRIM protein family, such as TRIM3 , TRIM16 , TRIM28 , and TRIM40 , have been reported for their roles in cancers 30, 31, 32, 33. However, to date, its role in tumor remains unclear.…”
Section: Resultsmentioning
confidence: 99%